Amphiscolytus — a new genus, and Amphiscolytini — a new tribe of Scolytidae (Coleoptera) for Dacryophthorus capensis Schedl - Mandelshtam, Michail Yu.; Beaver, Roger A. (Zootaxa, 2003)
A new genus Amphiscolytus and a new tribe Amphiscolytini are described to include Dacryophthorus capensis Schedl, 1971 — a poorly known species of Scolytidae (Coleoptera) with a unique set of features from South Africa. Amphiscolytus capensis (Schedl, 1971) is redescribed and figured.